The development of an aftermarket intercooler spray for turbocharged vehicles using ethylene glycol and hyaluronic acid - M.I.N, Ma'arof; G.T., Chala; Sathurshan, Suresh; Shaheerthana, Suresh (IOP Publishing, 2020)
Intercooler is used in motor vehicles to cool the air compressed by a turbocharger. Engine heat and weather condition commonly influence the efficiency of the intercooler, and this in turn affects the overall engine's power output. The objective of this study was to design and develop an autonomous cooling system for top-mounted intercooler. The system was powered by Arduino Uno microcontroller that gathers data from the temperature sensor and triggers the spraying mechanism automatically when required. Besides, the system could also be operated manually via a switch by the user. The experimental results showed that the efficiency of the normal intercooler without the spray cooling unit was improved from 56.52% to 90.72% and the minimum possible efficiency with the spray cooling unit was 32.38% more efficient. Upon using ethylene glycol as the spray medium, the system achieved 90.70% efficiency. Even so, hyaluronic acid had the most effective heat absorbing capacity as its efficiency was 90.72%. This proved that the cooling process through spray cooling unit had a vast improvement on the efficiency of the intercooling system. Generally, for all three independent variables, temperature drop increases with the increasing amount of pressure created by the additional pumps, hence, efficiency of the system increases. However, for hyaluronic acid, the efficiency is also dependent on its texture and viscosity. This newly designed portable plug-and-play intercooler spray unit would be beneficial to increase the performance of the intercooler by improving the heat exchange capacity of the unit. For future studies, other types of spray cooling medium or combinations of several cooling mediums could be tested.